2004
DOI: 10.1212/01.wnl.0000118304.08215.4c
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-antitrypsin deficiency alleles are not associated with cervical artery dissections

Abstract: The authors searched for the presence of alpha-1-antitrypsin (AAT) deficiency alleles PiZ and PiS in 74 patients with spontaneous cervical artery dissections (sCADs) and in 74 healthy control subjects. In both groups, the authors found four carriers of deficiency alleles. The connective tissue morphology of one additional patient with sCAD with PiZM genotype and her relatives was studied in skin biopsies. The PiZ allele did not segregate with morphologic alterations of the dermal connective tissue in the famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…38 Additionally, Konrad et al 38 found that the ␣ 1 -AT genotypes did not differ among cases and controls, as did Grond-Ginsbach et al 35 Connective Tissue Disease Three studies were identified from the same research group, with the same subjects being included in subsequent larger studies. 3,4,36 Connective tissue abnormalities were present in 55% (nϭ36/65) 4 and 68% (nϭ17/25) 3 in 2 studies, whereas none of the non-CAD ischemic controls in either study demonstrated such abnormalities.…”
Section: Genetic or Inborn Predisposition/disorders With A Familial Amentioning
confidence: 99%
“…38 Additionally, Konrad et al 38 found that the ␣ 1 -AT genotypes did not differ among cases and controls, as did Grond-Ginsbach et al 35 Connective Tissue Disease Three studies were identified from the same research group, with the same subjects being included in subsequent larger studies. 3,4,36 Connective tissue abnormalities were present in 55% (nϭ36/65) 4 and 68% (nϭ17/25) 3 in 2 studies, whereas none of the non-CAD ischemic controls in either study demonstrated such abnormalities.…”
Section: Genetic or Inborn Predisposition/disorders With A Familial Amentioning
confidence: 99%
“…14 Family III was included in a sequence analysis of COL5A1 in 19 patients with CAD. 15 The segregation of ␣-antitrypsin deficiency mutation PiZ was studied before in family V. 16 Family VI are whites from Argentina, family V is German-Swiss, and the other 5 families are from Germany. None of the families was related with each other.…”
Section: Patients and Clinical Diagnosismentioning
confidence: 99%
“…Despite a biological plausible a priori hypothesis, our results do not support a role for MTHFR/C677T in the aetiology of carotid dissection. Two other candidates, MMP-9 [28] and α 1 -antitrypsin deficiency [29], have been studied in carotid dissection but have not been replicated. Lack of studies therefore prevented these for inclusion into our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%